Study of phase composition on resorption glass-ceramic соatings for titanium - Шадріна, Галина Миколаївна; Саввова, Оксана Вікторівна; Шемет, Дарина Юріївна (Eastern-European Journal of Enterprise Technologies, 2014)
The problem of long-term knitting of bioactive glass-ceramic calcium silicate-phosphate coatings for titanium with a bone that constitutes about 6 months today, using foreign implants of this kind is considered in the paper. The solution to this problem by providing an appropriate resorption level of glass-ceramic coatings due to reproducing a certain ratio of phase-forming components is proposed. The purpose of this work was to study the effect of phase composition on resorption of glass-ceramic coatings for titanium. Bioactive calcium silicate-phosphate glass-ceramic coatings for titanium were synthesized; their crystallizability and solubility in the distilled water and physiological liquids were investigated in the paper. The resorption dependence on the calcium silicate-phosphate glass-ceramic coating structure and parabolic nature of the deposition kinetics of medium components on surfaces in the model liquid of the organism in vitro for a certain period were established. It is expedient to use the obtained results in the composition design of resorption bioactive glass-ceramic coatings for titanium in creating femoral endoprostheses with knitting terms from 3 months.